(untitled) (LEGAL DIALOGICA, 2025)
This research aims to understand and analyze the legal regulations and legal consequences of defamation crimes during the campaign stages of regional head elections. The research method used in this study employs the normative legal research method. It utilizes normative case studies in the form of legal behavior products, which examine the law. The main focus of the study is the law, conceptualized as norms or rules that apply in society and serve as a reference for everyone’s behavior. The research findings indicate that the legal regulation of defamation crimes is generally stipulated in the Indonesian Penal Code (KUHP). However, if the defamation crime occurs during the campaign activities of regional head elections, it is specifically governed by Law No. 10 of 2016. The legal consequences of defamation crimes during the campaign stage of regional head elections are regulated in several Indonesian legislations, including Articles 310 and 311 of the Penal Code concerning defamation or libel crimes, the Law on Information and Electronic Transactions (UU ITE), Law No. 7 of 2017, and Law No. 10 of 2016 on Regional Head Elections. The recommendations or suggestions provided by the researcher include that defamation crimes during the campaign stage of regional head elections can damage the democratic process, disrupt social harmony, and create public distrust. Therefore, prevention and handling must be conducted firmly and transparently. All parties, including campaign participants, election organizers, the media, and society, have an essential role in ensuring that campaigns are conducted fairly, honestly, and without defamation. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaturan hukum serta akibat hukum terhadap tindak pidana memfitnah dalam tahapan kampanye pemilihan kepala daerah. Metode penelitian yang digunakan dalam penelitian ini menggunakan metode penelitian hukum normatif (normative lawresearch). Menggunakan studi kasus normatif berupa produk perilaku hukum, yang mengkaji Undang-undang. Pokok kajiannya adalah hukum yang dikonsepkan sebagai norma atau kaidah yang berlaku dalam masyarakat dan menjadi acuan perilaku setiap orang. Hasil Penelitian menunjukkan bahwa Pengaturan hukum terhadap tindak pidana memfitnah telah diatur secara umum dalam KUHP, tetapi jika tindak pidana memfitnah tersebut terjadi dalam kegiatan kampanye pilkada maka lebih khusus diatur dalam Undang-Undang Nomor 10 Tahun 2016. Akibat hukum tindak pidana fitnah dalam tahapan kampanye Pemilihan Kepala Derah diatur dalam beberapa perundang-undangan di Indonesia diantaranya Kitab Undang-Undang Hukum Pidana pada pasal 310 dan 311 tentang tindak pidana pencemaran nama baik atau fitnah, Undang-Undang Informasi dan Transaksi Elektronik (UU ITE), Undang- Undang No 7 tahun 2017 dan Undang-Undang Nomor 10 Tahun 2016 Tentang Pemilihan Kepala Daerah. Rekomendasi atau Saran yang diberikan oleh peneliti yaitu, tindak pidana memfitnah dalam tahapan kampanye Pemilihan Kepala Daerah dapat merusak proses demokrasi, mengganggu kedamaian sosial, dan menciptakan ketidakpercayaan publik. Oleh karena itu, pencegahan dan penanganannya harus dilakukan secara tegas dan transparan. Semua pihak, mulai dari peserta kampanye, penyelenggara Pemilu, media, hingga masyarakat, memiliki peran penting dalam memastikan kampanye berlangsung dengan adil, jujur, dan tanpa fitnah.